Philosophical Perspectives: A Selection of Essays - ., K.T.K (Journal of Dharma, 1980)
M. Datta, Philosophical Perspectives, A Selection of Essays, Patna: Bharati Bhawan, First ed., 1972, pp. 184,. Rs. 25.